2005
DOI: 10.1111/j.1398-9995.2005.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs associated with persistent allergic rhinitis are reduced by levocetirizine

Abstract: The cost of persistent allergic rhinitis is substantial. Treatment with levocetirizine reduces the cost of persistent allergic rhinitis and its comorbidities to the society by 152.93/patient/month while improving symptoms and health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 23 publications
1
53
0
6
Order By: Relevance
“…Improvement in work/school productivity and daily activity measured by the WPAI-AS was significantly increased with DL compared with placebo. Other studies have found an effect on work productivity [34], but there was no objective assessment. DL treatment significantly reduced work absenteeism and presenteeism associated with symptoms of allergic rhinitis (IAR and PER).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in work/school productivity and daily activity measured by the WPAI-AS was significantly increased with DL compared with placebo. Other studies have found an effect on work productivity [34], but there was no objective assessment. DL treatment significantly reduced work absenteeism and presenteeism associated with symptoms of allergic rhinitis (IAR and PER).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly accepted that allergic rhinitis impairs work (10,84,113,1114,1115). It induces work absenteeism as well as a reduction in work productivity and presenteeism.…”
Section: Work Impairmentmentioning
confidence: 99%
“…Direct medical cost parameters (medications, doctor visits and hospitalizations) and time-lost parameters [work days and Usual Daily Activities (UDA)] related to PER and its co-morbidities were measured in a prospective 6-month study comparing levocetirizine and placebo in patients with moderate/severe PER (1115). From a societal perspective, the total cost of PER without long-term treatment was estimated at €355 per patient per month.…”
Section: The Costs Of Illness For Rhinitis and Its Co-morbiditiesmentioning
confidence: 99%
“…Very few studies have assessed the costs of managing allergic rhinitis in Europe (13). However, in one study, the direct medical cost of treating the disease in France was estimated to be Euro 510 million in 1997 (14), which is significantly higher than the costs for treating diseases such as epilepsy and colorectal cancer (13). Interestingly, in the US alone, it accounts for 3.5 million lost workdays and 2 million lost school-days each year (3).…”
Section: Allergic Rhinitismentioning
confidence: 99%